Delta-doped β-gallium oxide field-effect transistor. (18th April 2017) - Krishnamoorthy, Sriram; Xia, Zhanbo; Bajaj, Sanyam; Brenner, Mark; Rajan, Siddharth
Abstract: We report silicon delta doping in gallium oxide (β-Ga2 O3 ) grown by plasma-assisted molecular beam epitaxy using a shutter pulsing technique. We describe the growth procedures that can be used to realize high Si incorporation in an oxidizing oxygen plasma environment. Delta doping was adopted to realize thin (12 nm) low-resistance layers with a sheet resistance of 320 Ω/square (mobility of 83 cm 2 V −1 s −1, integrated sheet charge of 2.4 × 10 14 cm −2 ). A single delta-doped sheet of carriers was employed as a channel to realize a field-effect transistor with current I D, max = 236 mA/mm and transconductance g m = 26 mS/mm.